EDUCATION AND INNOVATION PROGRAM FOR WASTE MANAGEMENT INTO ORGANIC COMPOST FERTILIZER - Widowati Widowati; Jafron W. Hidayat; Satriyo Adhy; Eka Triyana (Pusat Studi Sosial dan Pengabdian Masyarakat Fisipkum Universitas Serang Raya, 2026)
This community service activity was prompted by the still low levels of public awareness and skills in managing organic waste, particularly in Mluweh Village, East Ungaran District, which has the potential to cause environmental problems. In fact, organic waste can be utilized as compost, which is valuable for agriculture and the environment. Therefore, this activity aims to increase the knowledge, skills, and awareness of the community in independently and sustainably processing organic waste into compost. The implementation methods included several stages: preparation through surveys and coordination with village authorities, dissemination to provide the community with initial understanding, compost-making training through demonstrations and hands-on practice, as well as monitoring and evaluation to assess the program’s success and sustainability. This activity involved a team of KKNT lecturers and students collaborating with village officials, PKK, youth organizations, and farmer groups. The implementation results showed an increase in community understanding and skills in processing organic waste into compost. In addition, the community has started to independently make compost and use it for agricultural and home garden needs. This activity also succeeded in raising public awareness of the importance of environmentally friendly waste management. Thus, this service program has made a positive contribution by reducing organic waste while supporting the creation of a clean, healthy, and sustainable environment